1997
DOI: 10.1007/s002130050420
|View full text |Cite
|
Sign up to set email alerts
|

A PET-study of [ 11 C]FLB 457 binding to extrastriatal D 2 -dopamine receptors in healthy subjects and antipsychotic drug-treated patients

Abstract: We recently developed [11C]FLB 457 a substituted benzamide with the very high affinity of 20 pM for D2-dopamine receptors in vitro. The aim of the present exploratory study was to examine the anatomical distribution of [11C]FLB 457 binding in the human brain and to determine extrastriatal D2-receptor occupancy in antipsychotic drug-treated patients. [11C]raclopride was used to obtain reference values for D2-dopamine receptor occupancy in the putamen. After IV injection of [11C]FLB 457 there was a high concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
93
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(100 citation statements)
references
References 38 publications
6
93
1
Order By: Relevance
“…Therefore, this would suggest that in nonhuman primates at a fairly high dose, clozapine interacts with D-2 receptors in all brain regions to a similar extent. Using 11 C-FLB 457, a similar striatal and thalamic occupancy level was reported by Farde et al (1997).…”
Section: Occupancy Of Extrastriatal D-2 Receptorssupporting
confidence: 64%
See 2 more Smart Citations
“…Therefore, this would suggest that in nonhuman primates at a fairly high dose, clozapine interacts with D-2 receptors in all brain regions to a similar extent. Using 11 C-FLB 457, a similar striatal and thalamic occupancy level was reported by Farde et al (1997).…”
Section: Occupancy Of Extrastriatal D-2 Receptorssupporting
confidence: 64%
“…For equilibrium studies, this region represents the free plus nonspecific radioligand concentration when measuring the bound to free ratios (Farde et al 1997). For kinetic studies, a reference region is used to calculate an index of specific binding, such as binding potential (BP) or distribution volume ratio (DVR) (Fowler et al 1998;Volkow et al 1999).…”
Section: Occupancy Of Extrastriatal D-2 Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One striking observation of our study was the conspicuously high level of [ 11 C]-( + )-PHNO binding in GP, a region that does not stand out as having a particularly high D 2 -receptor density in vitro and that has been scarcely studied using PET or SPECT. (Farde et al, 1997;Fujita et al, 1999;Mukherjee et al, 2002) but did not report on the visualization of GP in vivo. Only one PET study, using [ 11 C]FLB457 in human, clearly identified GP as a region with high D 2/3 binding, with a binding only slightly less than that measured in caudate-putamen (Okubo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The regions showing activation share reciprocal innervation with prefrontal cortex, amygdala and nucleus accumbens, each of which, in turn, are innervated by dopamine and other monoamine neurons (Groenwegen 1988;Su and Bentivoglio 1990;Vogt et al 1993;Lavin and Grace 1998). However, the thalamus, too, in human as in rat, shows evidence of dopamine and other monoamine innervation (Nieuwenhuys et al 1988;Farde et al 1997). Thus the effects observed may well be direct ones.…”
Section: Discussionmentioning
confidence: 99%